Long term outcome of neonatal meningitis. Issue 3 (1st May 2003) - Stevens, J P; Eames, M; Kent, A; Halket, S; Holt, D; Harvey, D
Abstract : Objectives: To quantify long term impairment after neonatal meningitis. Design: Longitudinal case-control study over 9–10 years. Subjects and methods: A total of 111 children who had suffered neonatal meningitis were seen and compared with 113 matched controls from their birth hospital and 49 controls from general practices. Assessments included the WISC III UK, movement assessment battery for children (mABC), audiometry, vision testing, and social and medical data. Statistical analysis was by multiple regression, analysis of variance, and χ 2 tests. Results: Some 10.8% of cases had a severe and 9% a moderate overall outcome compared with 0% and 1.8% for the hospital controls. The mean intelligence quotient (IQ) of the cases (88.8) was significantly less than that of the hospital controls (99.4) or the GP controls (99.6) . The mABC score was significantly worse for the cases (7.08) than the hospital (5) or GP (4) controls. Some 3.6% of cases had sensorineural hearing loss, 2.7% had persisting hydrocephalus; no controls did. Some 5.4% of cases and 1.7% of hospital controls had treatment for seizures. Conclusions: Severe neurodisability and milder motor and psychometric impairment result from neonatal meningitis. Both clinical follow up and comprehensive developmental assessment are needed after this disease.